EXPLORING TAX COMPLIANCE DYNAMICS: UNVEILING THE IMPACT OF PENALTIES, TAX AUTHORITY SERVICES, AND RISK PREFERENCES - Yan, Mei; Wangdra, Ronald (Universitas Putera Batam, 2024)
The aim of this research is to and determine the influence of tax penalties, tax authority services, and risk preference as a moderator in the influence of tax penalties on taxpayer compliance at the South Batam Tax Office. This research utilized primary data collected through the distribution of questionnaires to individual taxpayers registered at the South Batam Tax Office. Variables were measured responses using the Likert scale and a risk-assessment game. Additionally, oral interviews were conducted as part of the process. The total respondents numbered 117 taxpayers. Findings reveal that tax penalties do not significantly influence taxpayer compliance at the South Batam Tax Office, while tax authority services do have a significant impact on taxpayer compliance at the South Batam Tax Office. Furthermore, there is no significant moderation effect of risk preference on the influence of tax penalties regarding taxpayer compliance at the South Batam Tax Office.